Alticola lemminus - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Alticola lemminus (Miller, 1898). Proc. Acad. Nat. Sci. Philadelphia, 1898:369. TYPE LOCALITY: Siberia, Bering Strait, Plover Bay, Kelsey Station. DISTRIBUTION: NE Siberia from Chukotka area west through the Anadyr region to mouth of River Lena, and south throughout the Lena basin. COMMENTS: Subgenus Aschizomys. Corbet (1978c) transferred the species to Eothenomys, but Russian workers refered lemminus to Alticola (Gromov and Polyakov, 1977; Ognev, 1964; Pavlinov and Rossolimo, 1987). Earlier, Hinton (1926:279) recognized Aschizomys but speculated that the species "will prove to be a member of the E. rufocanus group." Miller (1940a:94) reexamined the holotype and identified it as "nothing more than an alcohol-discolored specimen of the extreme East Asian representative of Clethrionomys rufocanus." Based on our inspection of the holotype of lemminus, we endorse Ognev's (1964) allocation to Alticola, subgenus Aschizomys, and are impressed by its diagnostic features. Significant chromosomal and morphological differences between samples of A. lemminus from Chukotka and Yakutia regions led Bykova et al. (1978) to speculate that “lemminus" may be a composite of two species. Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 503, DOI: 10.5281/zenodo.7353098